(untitled) (Bangladesh Journal of Medical Science, 2020)
Anesthetic management including endotracheal intubation and neuroaxial blocks is challenging in patients with ankylosing spondylitis because of the stifness of vertebral joints. Peripheral blocks in these patients may be helpful although it is not common. A 56 year-old male patient with ankylosing spondylitis having the history of total knee arthroplasty and difficult airway management was operated for the contracted knee joint prosthesis. Anteromedialisation of tuberositas tibia was performed with combination of ultrasound guided psoas compartment block (PCB) and sciatic nevre block (SNB), and repeated forty days later because of the displacement of the osteotomy site. We conclude that PCB together with SNB may be performed for knee surgery in patients with severe ankylosing spondylitis. Bangladesh Journal of Medical Science Vol.19(4) 2020 p.772-774